Answer: The required simplified form of the given expression is
![f^4g^8.](https://img.qammunity.org/2020/formulas/mathematics/high-school/iujmufw63kkrpr5ngbpp6vgqozhohdql5x.png)
Step-by-step explanation: We are given to simplify the following expression :
![E=(fg^2)^4~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~(i)](https://img.qammunity.org/2020/formulas/mathematics/high-school/vw85f8ojvy3v0denbjsqolrmlk0hdydfph.png)
We will be using the following properties of exponents :
![(i)~(ab)^c=a^cb^c,\\\\(ii)~(a^b)^c=a^(bc).](https://img.qammunity.org/2020/formulas/mathematics/high-school/hr2dg0zzwzz6pb0xb33zp3trh3d45lk14h.png)
So, from (i), we get
![E\\\\=(fg^2)^4\\\\=f^4(g^2)^4\\\\=f^4g^(2*4)\\\\=f^4g^8.](https://img.qammunity.org/2020/formulas/mathematics/high-school/5q7k90hix2v3igtyb0rblct9b355ae6r0f.png)
Thus, the required simplified form is
![f^4g^8.](https://img.qammunity.org/2020/formulas/mathematics/high-school/iujmufw63kkrpr5ngbpp6vgqozhohdql5x.png)